KAJIAN BIBLIKA BALAK MEMANGGIL BILEAM BERDASARKAN BILANGAN 22:2-20 - Edwin Edwin (Jurnal Penggerak, 2024)
Balak saw Balaam as a prophet with extraordinary abilities, whose words were always on target and had great power. It is very important for a prophet of God to maintain consistent integrity and keep his heart pure from temptation. Balak has an accommodating nature, tends to exaggerate, and is diligent, but unfortunately he uses his strengths for the wrong purposes. Balak did not realize that in God's plan, Israel had been forbidden from attacking or harming the Moabites. The research method used to find answers to the research objectives is descriptive qualitative where the analysis process emphasizes the process of meaning. The results of the study concluded that God gave Balaam permission to follow his messenger Balak, this shows that even though Balaam left, his actions were still under God's control and permission. Balak planned evil against Israel by exploiting Balaam's strengths and weaknesses, God was able to use this to fulfill His plans.